Optimasi Penempatan dan Kapasitas PLTS on grid Pada Sistem Distribusi Radial Menggunakan Metode Algoritma Genetika Multi Konstrain - Muammar Zainuddin; Haditsah Annur (Jurnal Rekayasa Elektrika, 2019)
The photovoltaic grid-connected business opportunity offers challenges to power quality and voltage fluctuations in the distribution system. The purpose of this study is to optimize the location and power capacity of the grid-connected photovoltaic so that the voltage values are in accordance with the operating standards and meet the requirements of the connection techniques in the distribution system. The distribution system tested is the 69 Buses radial distribution feeder. The optimization uses three constraints namely voltage constraints, active power capacity constraints and total active power capacity constraints of the Grid-Connected Photovoltaic. The Optimization is carried out by considering the value of the percentage of the total active power of the Grid-Connected Photovoltaic capacity to the total load in the distribution system. The optimization results in the first simulation indicated seven grid locations with a total active power of 1.156 MW (38% PV) and produced a fitness value of 0.029. The second Simulation showed 7 locations with a total active power of 1.243 MW (41% PV) and produced a fitness value of 0.023. The Third simulation was identified with 11 locations with a total active power of 1.385 MW (46% PV) and produced a fitness value of 0.022. The best fitness value is the lowest value of the active power losses. The entry of a number of the Grid-Connected Photovoltaic System with distributed location can increase the voltage level in the distribution system.